Charge storage in the PANI-α-MnO2polymer-nanocomposite system - Izan Izwan, Misnon; Rajan, Jose (Elsevier Ltd, 2021)
Supercapacitors (SCs) store electrochemical energy with high specific power, faster charge response, and long cycle life at an electrode-electrolyte interface; however, with lower specific energy than commercial batteries. In this article, structural, morphological, surface and electrochemical properties of a polymer-nanocomposite in the PANI-α-MnO2 system has been systematically investigated. The α-MnO2was synthesized by molten salt methods and the polymeric composite was developed by in-situ polymerization. The materials were characterized by thermal analyses, X-ray and electron diffraction, FTIR spectroscopy, gas adsorption studies, scanning and transmission electron microscopy. The electrochemical properties of the materials before and after PANI modification are studied in 6 M KOH aqueous electrolyte employing cyclic voltammetry, galvanostatic charge-discharge cycling, and electrochemical impedance spectroscopy. A difference in charge storage mechanism from pseudocapacitive type to battery-type was observed upon PANI modification and the corresponding charge storage and charge kinetic parameters have been detailed.